2012
DOI: 10.1371/journal.pntd.0001470
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Based Models for Understanding and Forecasting Dengue Epidemics

Abstract: BackgroundDengue dynamics are driven by complex interactions between human-hosts, mosquito-vectors and viruses that are influenced by environmental and climatic factors. The objectives of this study were to analyze and model the relationships between climate, Aedes aegypti vectors and dengue outbreaks in Noumea (New Caledonia), and to provide an early warning system.Methodology/Principal FindingsEpidemiological and meteorological data were analyzed from 1971 to 2010 in Noumea. Entomological surveillance indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
175
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(198 citation statements)
references
References 50 publications
11
175
1
11
Order By: Relevance
“…A recent publication showed that secondary DENV-2 infections could result from more virulent clades than others, depending on the serotype of the primary infecting serotype, DENV-1 or DENV-3. 21 Under these conditions, the development dynamics of epidemics, the function of the implicated genotypes, and the intervals between the successive epidemics, 22 the immune and genetic status of the population, 23 and other environmental factors such as the population density, 24 the climate and density of mosquitoes of the Aedes genus, 25 could create specific situations in each endemic region and thus create many confounding factors. This could explain the differences in results shown in various publications on the theme of clinical presentation by serotype.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication showed that secondary DENV-2 infections could result from more virulent clades than others, depending on the serotype of the primary infecting serotype, DENV-1 or DENV-3. 21 Under these conditions, the development dynamics of epidemics, the function of the implicated genotypes, and the intervals between the successive epidemics, 22 the immune and genetic status of the population, 23 and other environmental factors such as the population density, 24 the climate and density of mosquitoes of the Aedes genus, 25 could create specific situations in each endemic region and thus create many confounding factors. This could explain the differences in results shown in various publications on the theme of clinical presentation by serotype.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a positive association between minimum temperature lagged by one month and dengue incidence 3,4,12,23,24 . Minimum temperature is thus a critical limiting factor in the development and maintenance of the vector population.…”
Section: Discussionmentioning
confidence: 99%
“…The variables used in these studies have been temperature, precipitation, relative humidity, wind velocity, and El Niño Southern Oscillation (ENSO) 2,3,4,5,6,7,8 . Studies have also evaluated dengue's relationship with socio-demographic and environmental variables in the municipality of Rio de Janeiro, Brazil, with a view to examining the effect of seasonal and annual factors on increases and decreases in dengue cases, as well as to make predictions 9,10,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de los diversos hallazgos sobre la asociación entre la transmisión del dengue y la precipitación, y de que en otros estudios no se ha observado tal relación (incluso se ha descrito como una relación no estacionaria y probablemente espuria) (37) Las demostraciones de la fuerte asociación entre la incidencia de dengue y los factores climáticos, han permitido la construcción de diversos modelos (15,(44)(45)(46). En particular, considerando las condiciones climáticas locales para un período de 11 años, en el presente estudio se desarrolló un modelo que captó los principales cambios en la tendencia en la incidencia de dengue en Medellín por efecto de la precipitación.…”
Section: Discussionunclassified